KARAKTERISASI BAKTERI DARI PERAKARAN Nepenthes mirabilis UNTUK PENGENDALIAN HAYATI Fusarium oxysporum - NFN Mardhiana; Muh. Adiwena; Ankardiansyah Pandu Pradana (Buletin Penelitian Tanaman Rempah dan Obat, 2020)
Phytopathogenic fungi Fusarium oxysporum causes significant yield losses in various spices plants. The fungus can be controlled with numerous types of antagonistic bacteria. This study aimed to determine the physiological characteristic and antagonistic properties of the bacterial from the roots of Nepenthes mirabilis, as a biological control to F. oxysforum. The study was conducted at the Plant Protection Laboratory, Faculty of Agriculture, the University of Borneo, Tarakan, from October to November 2017. Nutrient Agar medium was used to isolate antagonistic bacteria from the roots of N. mirabilis. Biosafety test against plants and mammals were conducted using hypersensitive and hemolysis analysis. The bacterial isolates passed from those tests were characterized further for their phenotype and physiological properties as well as their ability to inhibit the growth of F. oxysporum in a dual culture test  in  vitro.  The  results  showed  that  there  were  10  out  of26 bacterial isolates originated from N. mirabilis roots that were safe for plants and mammals. Physiological tests showed  that four  isolates  could produce the proteolytic enzyme, five isolates produced the chitinolytic enzyme, six isolates were able to dissolve phosphate, and four isolates could produce HCN. Furthermore, three isolates (Mrb2, Mrb6, and Mrb16) showed inhibitory activity against Fusarium spp. There were differences in the phenotype character and physiological activity between the Mrb2, Mrb6, and Mrb16 isolates, but all three have the potential to inhibit F. oxysporum.